Strategi Pengembangan Pariwisata Danau Tao Kecamatan Batang Onang Kabupaten Padang Lawas Utara - Sahdiah Harahap; Ferizaldi Ferizaldi; Syamsuddin Syamsuddin; T. Alfiady; Muslem Muslem (Indo Publishing, 2026)
Tourism development strategy is an effort to improve the quality and competitiveness of tourist destinations through the enhancement of promotion, accessibility, and supporting facilities and infrastructure. This study aims to analyze the tourism development strategy of Danau Tao in Batang Onang District, North Padang Lawas Regency, and identify the factors that hinder its implementation. This research employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving seven informants selected using purposive and accidental sampling techniques. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the promotion strategy has been implemented effectively through social media and community outreach, increasing public awareness of the destination. However, accessibility and tourism facilities remain inadequate due to poor road conditions, limited transportation, and insufficient supporting amenities. The main obstacles identified include budget constraints, weak government supervision, and low community participation. Therefore, the sustainable development of Danau Tao requires the integration of promotional activities, infrastructure improvement, stronger government oversight, and greater community involvement.